Consequences of Economic Inequality for the Social and Political Vitality of Society: A Social Identity Analysis. (11th December 2021) - Jetten, Jolanda; Peters, Kim; Álvarez, Belén; Casara, Bruno Gabriel Salvador; Dare, Michael; Kirkland, Kelly; Sánchez‐Rodríguez, Ángel; Selvanathan, Hema Preya; Sprong, Stefanie; Tanjitpiyanond, Porntida; Wang, Zhechen; Mols, Frank
Abstract : Economic inequality has been found to have pernicious effects, reducing mental and physical health, decreasing societal cohesion, and fueling support for nativist parties and illiberal autocratic leaders. We start this review with an outline of what social identity theorizing offers to the study of inequality. We then articulate four hypotheses that can be derived from the social identity approach: the fit hypothesis, the wealth‐categorization hypothesis, the wealth‐stereotype hypothesis, and the sociostructural hypothesis. We review the empirical literature that tests these hypotheses by exploring the effect of economic inequality, measured objectively by metrics such as the Gini coefficient as well as subjectively in terms of perceptions of economic inequality, on wealth categorization (of others and the self), the desire for more wealth and status, intergroup hostility, attitudes towards immigrants, prosocial behavior, stereotyping, the wish for a strong leader, the endorsement of conspiracy theories, and collective action intentions. As we will show, this research suggests that economic inequality may have even more far‐reaching consequences than commonly believed. Indeed, investigating the effects of economic inequality on citizens' sociopolitical behaviors may be increasingly important in today's turbulent political and social landscape.